Efficient Removal Of Bromate From Aqueous Solution Through Electrocoagualtion Using Aluminum Electrodes - Nasser M. Abu Ghalwa; Hossam El din El Nazer; Nader B. Farhat; Mahmud Sror (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
In this study the removal efficiency of bromate from aqueous solution using the electrocoagulation process was investigated. The effects of operational parameters such as initial pH, initial bromate concentration, current density, type electrode, salt concentration, and temperature on the removal efficiency have been studied. With an initial pH of 3.7, an initial bromate concentration of 100 mg/L, (current density 22.7 mA/cm2 using Al electrodes, salt concentration of 1.5 g/L NaCl and temperature of 25° C, The results showed that the removal percentage for bromate was 97% using Al/Al electrodes at 10 min. It can be concluded that electrocoagulation process by Al electrode is very efficient and clean process for bromate removal from Aqueous solution.